Physiological, Ecological, and Phylogenetic Characterization of Stappia, a Marine CO-Oxidizing Bacterial Genus - Weber, Carolyn F. (American Society for Microbiology, 2007)
Bacteria play a major role in marine CO cycling, yet very little is known about the microbes involved. Thirteen CO-oxidizing Stappia isolates obtained from existing cultures, macroalgae, or surf samples representing geographically and ecologically diverse habitats were characterized using biochemical, physiological, and phylogenetic approaches. All isolates were aerobic chemoorganotrophs that oxidized CO at elevated (1,000 ppm) and ambient-to-subambient concentrations (<0.3 ppm). All contained the form I (OMP) coxL gene for aerobic CO dehydrogenase and also the form II (BMS) putative coxL gene. In addition, some strains possessed cbbL, the large subunit gene for ribulose-1,5-bisphosphate carboxylase/oxygenase, suggesting the possibility of lithotrophic or mixotrophic metabolism. All isolates used a wide range of sugars, organic acids, amino acids, and aromatics for growth and grew at salinities from 5 to 45 ppt. All but one isolate denitrified or respired nitrate. Phylogenetic analyses based on 16S rRNA gene sequences indicated that several isolates could not be distinguished from Stappia aggregata and contributed to a widely distributed species complex. Four isolates (of strains GA15, HI, MIO, and M4) were phylogenetically distinct from validly described Stappia species and closely related genera (e.g., Ahrensia, Pannonibacter, Pseudovibrio, and Roseibium). Substrate utilization profiles, enzymatic activity, and membrane lipid composition further distinguished these isolates and supported their designations as new Stappia species. The observed metabolic versatility of Stappia likely accounts for its cosmopolitan distribution and its ability to contribute to CO cycling as well as other important biogeochemical cycles.